NFM-04. INITIAL MANAGEMENT STRATEGY AS A DISCRIMINATOR OF VISUAL OUTCOME IN CHILDREN PRESENTING WITH NEUROFIBROMATOSIS TYPE 1 AND OPTIC PATHWAY GLIOMA - RESULTS FROM A SOCIÉTÉ INTERNATIONALE D'ONCOLOGIE PÉDIATRIQUE EUROPE (SIOPE) CLINICAL TRIALS WORKSHOP. Issue 2 (22nd June 2018) - Azizi, Amedeo A; Walker, David A; Liu, Jo-Fen; Sehested, Astrid; Jaspan, Timothy; Simmons, Ian; Ferner, Rosalie; Grill, Jacques; Hargrave, Darren; Hernaiz-Driever, Pablo; Gareth Evans, D; Opocher, Enrico
Abstract: INTRODUCTION: Neurofibromatosis type 1 (NF1) is commonly associated with optic pathway gliomas (OPG) in childhood. Data on natural history are lacking and clinical trials of chemotherapy, so far, have not reported visual outcomes. In the 2014 SIOPE NF1-OPG Nottingham Workshop a convenience cohort was assembled and studied to inform a consensus on imaging and visual function classification and a schematic for recording visual acuity results. METHODS: An expert group of ophthalmologists, paediatric neurooncologists, neurofibromatosis specialists and neuro-radiologists identified 83 NF1-OPG patients (46 females, mean age 5·1 ± 2·6 years; 1-13·1 years) from six European countries. All patients (recruited between 2004 and 2012) were registered in the SIOP LGG-2004 trial. They were either observed or received treatment at diagnosis or after follow-up. Visual data were analysed to explore changes over time. RESULTS: 154 eyes in 77 patients were analysed. When starting treatment, visual acuity (VA) was worse in patients being treated at diagnosis (p=0·046). VA remained unchanged in the observation group. Compared to patients treated at diagnosis, children treated after observation less frequently developed further vision loss or dropped to near-blindness/blindness, indicating a better overall visual status at end of treatment. Of 16 patients worsening during observation, Vincristine/Carboplatin could improve vision in 7. CONCLUSIONS: Initial management strategy determined different visual outcomes, justifying criteria for observation versus immediate or delayed treatment in future trials with primary visual outcome measures. The adverse outcome for those treated immediately may suggest unnoticed, irreversible nerve damage advocating initiation of trials seeking to recognise and reverse incipient nerve damage.